Transformation Towards a Clean Digital Economy by Optimizing Non-Cash Transactions as an Instrument to Prevent Corruption - Wibisono, Sonny; Subiyantoro, Heru (Indonesian Journal of Multidisciplinary Science, 2025)
The transformation towards a digital economy in Indonesia presents a strategic opportunity to enhance financial transparency and combat corruption through non-cash transactions. Despite initiatives like the National Non-Cash Movement (GNNT) and advancements in digital payment systems such as QRIS, cash transactions remain dominant due to infrastructure disparities, low digital literacy, and entrenched cultural habits. This study examines the role of non-cash transactions in preventing corruption by leveraging digital footprints for real-time monitoring and accountability. Using a normative legal research method, the study analyzes regulations like Law Number 8 of 2010 on Money Laundering Prevention, alongside secondary data from institutions such as Bank Indonesia and the Corruption Eradication Commission (KPK). Findings reveal that digital transactions significantly reduce corruption risks by enabling transparent financial tracking, as evidenced by successful implementations like e-budgeting in DKI Jakarta. However, challenges persist, including cybersecurity threats and uneven policy coordination. The research underscores the need for stronger infrastructure, public education, and cross-sector collaboration to foster inclusive digital adoption. Strategic recommendations include enhancing regulatory frameworks, expanding digital literacy programs, and incentivizing private-sector innovation. These measures aim to create a resilient digital economy that prioritizes transparency, accountability, and equitable access, ultimately reducing corruption and strengthening public trust in financial governance.